Leaf antioxidant machinery stimulation by Meloidogyne javanica infestation: A case study on Cucumis melo seedlings - Tsaniklidis, Georgios; Chatzistathis, Theocharis; Fanourakis, Dimitrios; Nikoloudakis, Nikolaos; Kotsiras, Anastasios; Delis, Costas; Tzortzakakis, Emmanuel A. (My University, 2021)
Following nematode infestation, leaf-localized responses are vital not only as early infection signs but also as an indication of actions required to preserve crop productivity. In this context, the leaf-level physiological responses of cantaloupe seedlings were evaluated after 40 consecutive days of cultivation under different Meloidogyne javanica juveniles (J2s) inoculation regimes (0, 100, and 850 J2s plant−1). Leaf growth parameters and photosynthetic pigments (chlorophyll, carotenoids) content were not affected by J2s infestation, while foliar Potassium concentration significantly declined. The RuBIsCo activase gene expression was negatively associated with the J2s inoculation level. Total flavonoids, total phenolics, lipid peroxidation indexes, phenylalanine ammonia-lyase activity, as well as, ascorbate peroxidase gene transcription, were higher in the inoculated plants (regardless of the J2s inoculant level). Taken together, present data indicate that J2s infestation impacts primarily the Potassium levels in leaves. Additionally, a substantial stimulation of the plant antioxidant machinery (independent of the nematode infestation intensity) is triggered. Finally, it was established that the transcriptional regulation of the RuBIsCo activase 1 gene under biotic stress has the capacity to be employed as a potential stress indicator marker.
Keywords: Antioxidant defense; Biotic stress; Melon; Meloidogyne javanica; Photosynthesis; Root-knot nematode